A commentary of “Using satellites to map trees”: 10 remarkable discoveries from 2020 in Nature - Huang, Huaguo (Fundamental research (Beijing), 2022)
Brandt et al. reported the results of their analysis from high-resolution satellite images, covering more than 1.3 million square kilometers of the Western Sahara and Sahel in West Africa. They mapped the locations and sizes of approximately 1.8 billion trees. Prior to this, scientists had never made such a detailed map of trees in such a large area. Commercial satellites have begun to collect data and can detect small ground objects that are 1 square meter or less in size. Therefore, the field of terrestrial remote sensing may have a significant advance from mainly a comprehensive landscape-scale measurement to mapping the position and canopy size of each tree at a regional or even global scale. This progress will revolutionize how we think, monitor, simulate, and manage the global terrestrial ecosystem.①①Original source in Chinese: Huaguao Huang, Using satellites to map trees, Bulletin of National Natural Science Foundation of China. 35 (2) (2021) 239-240.